Clinical and radiological evaluation of the Bristow–Latarjet procedure in patients with 30 or more years of follow-up - Arnaldo Amado Ferreira Neto, MD, PhD; Mauro Emilio Conforto Gracitelli, MD, PhD; Jorge Henrique Assunção, MD, PhD; Fernando Brandão de Andrade e Silva, MD, PhD; Verônica Yulin Prieto Chang, MD; Eduardo Angeli Malavolta, MD, PhD (JSES International)
Background: The Bristow–Latarjet surgery is the procedure most performed for recurrent anterior shoulder dislocation. There are few studies with a follow-up of more than 20 years. Because it is a nonanatomical technique, there is interest in knowing the clinical and radiological results and the rates of complications in the long term. Methods: We performed a retrospective case series study. Patients with recurrent anterior dislocation of the shoulder who underwent the Bristow–Latarjet procedure were included and followed-up clinically for at least 30 years. We evaluated clinical scores—the Rowe, Western Ontario Shoulder Instability, Single Assessment Numeric Evaluation, and visual analog scale—as well as clinical outcomes: the recurrency (dislocation or subluxation) and seizure. Screw and graft positioning were assessed by computed tomography, the degree of arthropathy by radiography, and subscapularis fatty degeneration as rotator cuff tears by magnetic resonance imaging. Both clinical scores and imaging were obtained at 30 years of surgery. Results: Twenty-seven patients (30 shoulders) were evaluated, with a mean follow-up of 35 ± 4.5 years. The scores obtained were 88.28 ± 15.9 by Rowe, 208 ± 244.2 by the Western Ontario Shoulder Instability examination, 92.5% ± 10.4% by the Single Assessment Numeric Evaluation, and 0.45 ± 1.3 by the visual analog scale. The recurrence rate was 13.3%, with all patients presenting subluxations and no new dislocations. All grafts were positioned below the glenoid equator. In 82.4% of the cases, the grafts were aligned with the articular surface, 5.9% were medially deviated, and 11.8% were laterally deviated. Consolidation occurred in 76.5% of the cases. The screws presented bicortical fixation in 76.5% of the shoulders and inclination in the axial plane of less than 15° in 64.7%. A total of 58.8% of the cases presented with glenohumeral arthropathy, and 75% of the magnetic resonance imagings showed the absence of fatty degeneration. Conclusion: Bristow–Latarjet surgery demonstrates excellent clinical results in most patients after 30 years of follow-up. The recurrence rate is low, as is the complication rate. Glenohumeral arthropathy occurs in most patients without significant clinical repercussions.